Maharah al-Qira'ah Learning Planning and Strategies in Improving Islamic Understanding - Mira Hartati; Abdul Halim Hanafi (Program Pascasarjana UMSB, 2022)
The learning process is a complex activity, so careful planning is needed so that it can run systematically and more organized. In Arabic learning, the term learning planning is better known as